The Pitch: Managers’ Disclosure Choice during Initial Public Offering Roadshows - Blankespoor, Elizabeth; Hendricks, Bradley E.; Miller, Gregory S. (The Accounting Review, 2023)
ABSTRACT We examine firm disclosure choice during the initial public offering (IPO) roadshow presentation to understand the informativeness of a management presentation designed to attract investors. Although firms submit a comprehensive registration filing during the IPO, managers also prepare a roadshow presentation, which is shorter and typically allows managers more autonomy to select the information released and how it is discussed. We find that IPO roadshows have significantly more positive, less negative, and less uncertain language than the SEC filing. Using machine learning to classify roadshow sentences into five major topics from the registration statement, we find that roadshows differ in both the topics selected and the language used within each topic. We then examine the predictive ability of the roadshow language, finding that roadshow language predicts future accounting performance, whereas filing language does not. These results highlight the informational role of management presentations, despite the flexibility they grant managers. JEL Classifications: M41; G10; M13.